Control of platform monopolization in the digital economy: The implication of open innovation - Sergey Silvestrov; Vladimir Starovoitov; Dmitrii Firsov (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study aims to develop scientifically sound proposals and recommendations for implementing the principles and characteristics of digital monopolies and determine the patterns and relationships of individual products. To achieve the goal, methodological approaches used included correlation analysis. The results are methodological justifications to determine the key principles of digital monopolies within the service approach. The scientific novelty of the results is to identify the synergetic relationship of individual products of digital companies, which can be used to build an appropriate antimonopoly policy of the United States. The practical significance of the results consists of approbation of the proposed principles of digital monopolies on the example of the relationship of Google's selected products.
Keywords: 650; digital monopolies; IT corporations; Alphabet; Google; YouTube; open innovation